Exploring the substrate scope of histone demethylases - Bonnici, J (2020)
Post-translational modifications of histones play key roles in regulation of eukaryotic transcription and in epigenetics. Lysine methylation of histones is a dynamic balance between activity of methyl transferases and demethylases (KDMs). Fe(II) 2-oxoglutarate (2OG)-dependent Jumonji C (JmjC)-KDMs are current targets for medical chemistry. Defining the extent and role of their substrates is important from a translational perspective and is of basic scientific interest.